Lipidomic Signatures of Dairy Consumption and Associated Changes in Blood Pressure and Other Cardiovascular Risk Factors Among Chinese Adults. Issue 8 (26th April 2022) - Yun, Huan; Sun, Liang; Wu, Qingqing; Luo, Yaogan; Qi, Qibin; Li, Huaixing; Gu, Weiqiong; Wang, Jiqiu; Ning, Guang; Zeng, Rong; Zong, Geng; Lin, Xu
Abstract : Background: Omics data may provide a unique opportunity to discover dairy-related biomarkers and their linked cardiovascular health. Methods: Dairy-related lipidomic signatures were discovered in baseline data from a Chinese cohort study (n=2140) and replicated in another Chinese study (n=212). Dairy intake was estimated by a validated food-frequency questionnaire. Lipidomics was profiled by high-coverage liquid chromatography-tandem mass spectrometry. Associations of dairy-related lipids with 6-year changes in cardiovascular risk factors were examined in the discovery cohort, and their causalities were analyzed by 2-sample Mendelian randomization using available genome-wide summary data. Results: Of 350 lipid metabolites, 4 sphingomyelins, namely sphingomyelin (OH) C32:2, sphingomyelin C32:1, sphingomyelin (2OH) C30:2, and sphingomyelin (OH) C38:2, were identified and replicated to be positively associated with total dairy consumption (β=0.130 to 0.148; P <1.43×10 −4 ), but not or weakly with nondairy food items. The score of 4 sphingomyelins showed inverse associations with 6-year changes in systolic (−2.68 [95% CI, −4.92 to −0.43]; P =0.019), diastolic blood pressures (−1.86 [95% CI, −3.12 to −0.61]; P =0.004), and fasting glucose (−0.25 [95% CI, −0.41 to −0.08]; P =0.003). Mendelian randomization analyses further revealed that genetically inferred sphingomyelin (OH) C32:2 was inversely associated with systolic (−0.57 [95% CI, −0.85 to −0.28]; P =9.16×10 −5 ) and diastolic blood pressures (−0.39 [95% CI, −0.59 to −0.20]; P =7.09×10 −5 ). Conclusions: The beneficial effects of dairy products on cardiovascular health might be mediated through specific sphingomyelins among Chinese with overall low dairy consumption.